Long-term outcomes of silicone metacarpophalangeal arthroplasty: a longitudinal analysis of 325 cases. (December 2018) - Boe, Chelsea; Wagner, Eric; Rizzo, Marco
An analysis was conducted of 325 consecutive metacarpophalangeal arthroplasties prospectively collected using a single institution's total joints registry over a 14-year time period to characterize long-term radiographic and functional outcomes. Patients were followed for a mean of 7.2 years (2–18) or until revision. The 5-, 10- and 15-year survival free from revision were 98%, 95% and 95%, respectively. The 5-, 10- and 15-year survival rates free from radiographic implant fracture were 93%, 58% and 35%, respectively. The 5-, 10- and 15-year survival rates free from coronal plane deformity greater than 10° were 81%, 37% and 17%, respectively. Patients had significant improvements in their postoperative pain levels and metacarpophalangeal arc of motion. Neither implant fracture, nor coronal plane deformity >10° had a significant association with worse function. Overall, pain relief and functional improvement are reliable, though silicone implants do not protect from progression of coronal plane deformity and have a high fracture rate. Level of evidence: IV